ChemInform Abstract: A Direct Synthesis of Selenophenes by Cu‐Catalyzed One‐Pot Addition of a Selenium Moiety to (E, E)‐1, 3‐Dienyl Bromides and Subsequent Nucleophilic Cyclization. Issue 8 (February 2015) - Maity, Pintu; Kundu, Debasish; Roy, Rajdip; Ranu, Brindaban C.
Abstract An efficient synthesis of selenophenes and thiophenes (XIII) via coupling of 1, 3‐dienyl bromides (I) with KSeCN and thiourea, resp., is described.